Quantitative Genetics, Genomics and Plant Breeding. - Kang, M. S. (CAB International, 2002)
This text provides an overview of the rapidly developing integration and interdependence of quantitative genetics, genomics, and bioinformatics, and their application to plant breeding. Authors include international authorities from around the world.